Quantum engineering : theory and design of quantum coherent structures - Zagoskin, Alexandre M. (Cambridge : Cambridge University Press, 2011)
"Quantum engineering - the design and fabrication of quantum coherent structures - has emerged as a field in physics with important potential applications. This book provides a self-contained presentation of the theoretical methods and experimental results in quantum engineering. The book covers topics such as the quantum theory of electric circuits, theoretical methods of quantum optics in application to solid state circuits, the quantum theory of noise, decoherence and measurements, Landauer formalism for quantum transport, the physics of weak superconductivity and the physics of two-dimensional electron gas in semiconductor heterostructures. The theory is complemented by up-to-date experimental data to help put it into context. Aimed at graduate students in physics, the book will enable readers to start their own research and apply the theoretical methods and results to their current experimental situation"--
Machine generated contents note: 1. Quantum mechanics for quantum engineers; 2. Superconducting quantum circuits; 3. Quantum devices based on two-dimensional electron gas; 4. Superconducting multiqubit devices; 5. Noise and decoherence; 6. Applications and speculations; Appendix; Index.
Formerly CIP.
Includes bibliographical references (p.315-326) and index.
Keywords: Quantum theory; Quantum engineering